2007
DOI: 10.1002/jcb.21552
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathogenesis and therapeutic targets in epithelial ovarian cancer

Abstract: Ovarian cancer, the most aggressive gynecologic cancer, is the foremost cause of death from gynecologic malignancies in the developed world. Two primary reasons explain its aggressive behavior: most patients present with advanced disease at diagnosis, and die of recurrences from disease that has become resistant to conventional chemotherapies. In this paper on epithelial ovarian cancer (EOC), we will review molecular alterations associated with the few precursor lesions identified to date, followed by the more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 70 publications
2
35
0
1
Order By: Relevance
“…The past few years have seen an enormous growth in our understanding of the mechanisms that regulate drug-induced apoptosis, arrest the cell cycle, and inhibit angiogenesis, and thus influence chemosensitivity. 41 One possible target to enhance chemosensitivity is to prevent drug efflux in cancer cells by blocking ATP-binding cassette transporters, 42 but a Phase III clinical trial showed no improvement in survival. Inhibitors of glutathione, 43 angiogenic molecules 44 and growth factor receptors 45 are the new therapeutic targets for treating ovarian cancer, but the outcomes are controversial and need further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The past few years have seen an enormous growth in our understanding of the mechanisms that regulate drug-induced apoptosis, arrest the cell cycle, and inhibit angiogenesis, and thus influence chemosensitivity. 41 One possible target to enhance chemosensitivity is to prevent drug efflux in cancer cells by blocking ATP-binding cassette transporters, 42 but a Phase III clinical trial showed no improvement in survival. Inhibitors of glutathione, 43 angiogenic molecules 44 and growth factor receptors 45 are the new therapeutic targets for treating ovarian cancer, but the outcomes are controversial and need further studies.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is of importance as platinum resistance ultimately becomes the dominant problem for most patients with ovarian cancer. The approach described here holds promise in that it may be coupled to molecularly targeted therapies that can either reverse acquired platinum resistance or enhance intrinsic platinum sensitivity (Gordon et al, 2005;Schilder et al, 2005;Alvero et al, 2006;Appleton et al, 2007;Cannistra et al, 2007;Chien et al, 2007). This approach may feasibly enhance efficacy to the point that survival gains may become worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced-stage disease display aggressive chemoresistant behavior with patients demonstrating a shorter median survival rate [11,12].…”
Section: Discussionmentioning
confidence: 99%